Working safely with electricity - Huber, Dan; Bergwall, Charles; Hudson, David M.; Bergwall Productions (Chadds Ford, PA: Bergwall Productions, 1992)
These videos discusses about working safety with electricity during working hours
part 1. Electricity can kill - part 2. Shock emergency - part 3. Importance of grounding - part 4. Emergency response
Author, Dan Huber; producer, Charles Bergwall; editor, David M. Hudson
Host: Jim Scoppelitis
Keywords: Electricity -- Safety measures; Electricity -- Psychological effect; Electrical injuries -- Prevention; Electric shock -- Prevention